THE EFFECTIVENESS OF LEARNING STRATEGIES TYPE OF GIVING QUESTION AND GETTING ANSWERS TOWARD MATHEMATICS LEARNING OUTCOMES IN STUDENS CLASS XI OF SMK NEGERI 1 PUNDONG BANTUL DISTRICT IN EVEN SEMESTER OF ACADEMIC YEAR 2015/2016 - Elly Puspitaningsih; Widayati Widayati (Universitas Ahmad Dahlan, 2017)
This research was done because there are many students who are less active in learning. Students do not want to ask about the material they have not understood that the learning outcomes obtained less than the maximum. This study aims to determine the effectiveness of mathematics learning by using strategies question giving and getting answer compared using expository strategy on learning outcomes math of students in class XI of SMK Negeri 1 Pundong Bantul District even Semester in the academic year 2015/2016. This research design was control group posttest-only design. The population in this research was a class XI TKJ A, XI TKJ B, and XI TITL A student of SMK Negeri 1 Pundong. Samples were taken using random sampling techniques derived class XI TKJ B as an experiment class and class XI TKJ A as the control class. The data collection is done with test method. Testing instrument using validity and reliability. Data were analyzed using analysis prerequisite test including normality test with Chi-square formula, homogeneity test with Bartlett's test, and hypothesis testing using t-test. Based on calculations with significance level and degrees of freedom of 60, the conclusion that: (1) there are differences in learning outcomes of students learning math using active learning strategies type of giving question and getting answer by learning to use expository strategies. This is indicated by the results of the first test hypothesis that that is .(2) learning to use active learning strategies type of giving question and getting answer more effective than learning to use strategies expository. It is shown from the results of the second test the hypothesis that that is .